Validity Evidence for Progress Monitoring With Star Reading: Slope Estimates, Administration Frequency, and Number of Data Points - Bulut, Okan; Cormier, Damien C. (Frontiers in Education, 2018)
The increasing use of computerized adaptive tests (CATs) to collect information about students’ academic growth or their response to academic interventions has led to a number of questions pertaining to the use of these measures for the purpose of progress monitoring. Star Reading is an example of a CAT-based assessment with considerable validity evidence to support its use for progress monitoring. However, additional validity evidence could be gathered to strengthen the use and interpretation of Star Reading data for progress monitoring. Thus, the purpose of the current study was to focus on three aspects of progress monitoring that will benefit Star Reading users. The specific research questions to be answered are: (a) how robust are the estimation methods in producing meaningful progress monitoring slopes in the presence of outliers; (b) what is the length of the time interval needed to use Star Reading for the purpose of progress monitoring; and (c) how many data points are needed to use Star Reading for the purpose of progress monitoring? The first research question was examined using a Monte Carlo simulation study. The second and third research questions were examined using real data from 6,396,145 students who took the Star Reading assessment during the 2014-2015 school year. Results suggest that the Theil-Sen estimator is the most robust estimator of student growth when using Star Reading. In addition, it appears that five data points and a progress monitoring window of approximately 20 weeks appear to be the minimum parameters for Star Reading to be used for the purpose of progress monitoring. Implications for practice include adapting the parameters for progress monitoring according to a student’s current grade-level performance in reading.